Optimal designs of the exponentially weighted moving average (EWMA) median chart for known and estimated parameters based on median run length. Issue 7 (3rd July 2022) - Chong, Z. L.; Tan, K. L.; Khoo, Michael B. C.; Teoh, W. L.; Castagliola, P.
Abstract: In the literature, the sole dependence on the ARL as the performance measure of a control chart has received much criticism. This is because interpretation based on the ARL alone can be misleading, as the shape and skewness of the run-length distribution vary according to the magnitude of the process mean shift. Therefore, we consider the median run length (MRL) performance measure for optimal EWMA median chart when process parameters are known and estimated. We provide an illustrative example to show the application of the optimal EWMA median chart based on expected median run length (EMRL).